Is Communication a Vidya or an Avidya according to Hinduism? - Adhikary, Nirmala (Bodhi: An Interdisciplinary Journal, 2025)
This article discusses the discipline of communication as a vidya (true knowledge) according to Hinduism. The present article is a revisit to an older article (Adhikary, 2010). It presents Hindu perspective on communication concerning the Sadharanikaran Model of Communication, employing the message- or artifactoriented research approach. This article observes moksha as the highest of purushartha chatustaya (four goals of human life) based on Hindu belief and presents an appraisal on verbal communication as a means for attaining moksha-in-life. In addition, the article recognizes different kinds of yoga, such as jnanayoga, karmayoga, and bhaktiyoga in Hinduism and examines whether the process of communication qualifies to be regarded as the sancharyoga. Then, it concludes yoga is a communication model, and the discipline of communication is a vidya itself, being relied on perspectives of Hinduism.